2011
DOI: 10.1186/1479-5876-9-195
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA modulation in complex regional pain syndrome

Abstract: BackgroundAberrant expression of small noncoding RNAs called microRNAs (miRNAs) is a common feature of several human diseases. The objective of the study was to identify miRNA modulation in patients with complex regional pain syndrome (CRPS) a chronic pain condition resulting from dysfunction in the central and/or peripheral nervous systems. Due to a multitude of inciting pathologies, symptoms and treatment conditions, the CRPS patient population is very heterogeneous. Our goal was to identify differentially e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
127
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(135 citation statements)
references
References 43 publications
7
127
0
Order By: Relevance
“…n ¼ 6-8 per group. previous reports [10], suggesting that suppression of proinflammatory cytokine activity could be a promising clinical approach.…”
Section: Discussionmentioning
confidence: 99%
“…n ¼ 6-8 per group. previous reports [10], suggesting that suppression of proinflammatory cytokine activity could be a promising clinical approach.…”
Section: Discussionmentioning
confidence: 99%
“…Leinders et al, 2016 37 recently found that several systemic mirco-RNAs (miR), specifically miR-103, miR-151, and miR-let-7d, were downregulated in patients with fibromyalgia whereas cutaneous miR-let-7d was elevated in patients with reduced small nerve fiber density. miR-let7d has previously been found to be associated with chronic pain in patients with complex regional pain syndrome 38 and to affect the endogenous opioid system 39 , which is known to be impaired in, e.g. KOA 15 or fibromyalgia 40 .…”
Section: Thermal Testing In Knee Osteoarthritismentioning
confidence: 99%
“…When studying gene expression profiles in common conditions with subclinical histopathology, such as IBS, high sensitivity and accuracy (reproducibility) are needed, as perturbations in gene expression profiles are often subtle [1][2][3] . miRNAs have been identified as both diagnostic and functional targets in IBS 4,5 , and we are particularly interested in assessing their use as circulating biomarkers of IBS-associated biological perturbations 3,4,6,7 . The clinical utilization of circulating biomarkers is of current interest due to the ease and minimally invasive nature of the collection of the biomarkers' source (e.g., peripheral blood) from patients.…”
Section: Introductionmentioning
confidence: 99%